Efficiency of the Strategic Planning of the Human Resources (System of Libyan Universities as a Model) - Mahmoud Mohammed; Salem Ali Salem Matoug; Asma Abdul Rahman (International Journal of Science and Research (IJSR), 2024)
Volume 5 Issue 10, October 2016, 1398 - 1401